2021
DOI: 10.32800/amz.2021.19.0007
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of chewing lice (Phthiraptera: Amblycera and Ischnocera) of the birds of Peru

Abstract: Peru is one of the countries with the highest diversity of birds worldwide, having about 1,876 species in its territory. However, studies focused on chewing lice (Phthiraptera) have been carried out on only a minority of bird species. The available data are distributed in 87 publications in the national and international literature. In this checklist we summarize all the records to date of chewing lice on wild and domestic birds in Peru. Among the 301 species of birds studied, 266 species of chewing lice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…According to the list of malophagous lice species recorded in Peru by Minaya et al (2021), it can be inferred that the malophagous lice species identified in the present study constitute new records for the Department of Loreto and for Peru. Table 1 records nine new species for Peru and four new hosts.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…According to the list of malophagous lice species recorded in Peru by Minaya et al (2021), it can be inferred that the malophagous lice species identified in the present study constitute new records for the Department of Loreto and for Peru. Table 1 records nine new species for Peru and four new hosts.…”
Section: Discussionsupporting
confidence: 50%
“…Peru has the second greatest diversity of birds in the world, with 1,892 species currently identified in its territory (Plenge, 2023). However, studies related to malophagous lice have only been carried out in 16 % of bird species, thereby limiting the information available regarding the biodiversity of these parasites in this setting (Minaya et al, 2021). The region of Loreto in the Peruvian Amazon has the greatest ornithological diversity in Peru, with the presence of 55 % of the total number of birds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation